Efektivitas Strategi Pemasaran Bank Syariah dalan Menarik Minat Nasabah Muda - Zuhrinal M. Nawawi; Salsabila Sofiya Wardani (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study uses a qualitative method to examine the effectiveness of marketing strategies implemented by Islamic banks in attracting young customers. The background of this research is based on the significant growth of the Islamic banking sector in Indonesia, which has not yet fully optimized the potential of the youth market segment. Data were collected through in-depth interviews with marketing managers and young customers, as well as documentation of the promotional strategies employed. The findings reveal that marketing strategies emphasizing Islamic values, service digitalization, and social media campaigns significantly influence young customers’ interest. However, some challenges were also identified, such as low Islamic financial literacy among the youth and limited product innovation tailored to their needs. This study recommends strengthening Islamic financial education, collaborating with youth communities, and developing technology-based products and services so that Islamic banks can be more competitive in attracting young customers. With a more adaptive and communicative approach, Islamic banks have the potential to become the preferred choice for the younger generation in the future.